(untitled) (Religious dialogue and cooperation, 2026)
Religious fundamentalism represents a highly contentious and evolving topic within contemporary European culture. This research examines the phenomenon through its historical, political, and cultural dimensions, encompassing various religious traditions including Catholicism, Protestantism, Orthodoxy, and Islam. Fundamentalism is viewed as a response to modernisation, secularisation, and globalisation, while also serving as an ideological mechanism for maintaining identity and tradition. Particular emphasis is placed on its interplay with national identity, pluralism, and democracy, as well as the resulting cultural conflicts. Migrations, the influence of media and emerging technologies, and the institutional response of the European Union are identified as pivotal elements shaping the current dynamics of religious fundamentalism. The ultimate determination is that fundamentalism should not be perceived merely as an external threat, but rather as an intrinsic component of European cultural and political reality, which concurrently challenges and redefines the continent’s future.